Case report: Satralizumab as an adjunctive therapy for AQP-4 antibody and MOG antibody dual-negative optic neuritis in a third-trimester pregnancy case - Sun, Chuanbin; Liu, Zhe (Frontiers in Medicine, 2024)
The treatment of demyelinating optic neuritis (DON) in pregnant patients is challenging, especially when there is poor or no response to intravenous methylprednisolone pulse (IVMP) therapy or adjunctive treatments such as intravenous immunoglobulin (IVIG) therapy. We herein report a case of a 28-year-old pregnant woman who experienced sequential severe vision loss in both eyes. She presented to a local hospital with the main complaint of sudden, painless vision loss in the left eye and was diagnosed with DON in the left eye. However, she did not receive orbital MRI or IVMP therapy due to safety concerns. Upon admission to our hospital, her visual acuity was 20/30 in the right eye and there was no light perception in the left eye. Her right eye vision deteriorated rapidly, declining to 20/1,000 one day after the admission. The ophthalmic examination revealed a normal anterior segment and a swollen optic disk in the right eye and a dilated pupil with a relative afferent pupillary defect and a swollen optic disk in the left eye. The serological tests for common pathogens, including the aquaporin-4 antibody (AQP-4 Ab), myelin oligodendrocyte glycoprotein antibody (MOG-Ab), and other common autoantibodies, were all negative. The patient was clinically diagnosed with DON in both eyes and received 7 days of IVMP therapy and 4 days of IVIG therapy, but showed no visual improvement. A three-dose regimen of satralizumab 120 mg was then administered subcutaneously during the acute stage of DON, in combination with a slowly tapered oral methylprednisolone regimen. Moreover, 2 months after the first injection of satralizumab, the patient naturally gave birth to a healthy female infant weighing 2,305 g at 36 weeks and 1 day of gestation. Her visual acuity improved to 20/500 in both eyes and slightly increased to 20/320 in both eyes 2 months later. Her visual acuity remained stable during subsequent follow-up visits. The infant was fed formula milk powder and developed normally. No systemic or ocular side effects related to satralizumab therapy were observed in the patient or her fetus during the 9-month follow-up. Our findings in this case suggest that satralizumab may be a safe and efficient adjunctive therapy for pregnant patients with DON who poorly respond to IVMP and IVIG therapy, even in cases of dual-negative AQP-4 Ab and MOG-Ab.